Comparative Study of Student Morality in Islamic Boarding Schools and Non-Islamic Boarding Schools - Alfi Lailiatul Fauziyah; Ahmad Aly Syukron Aziz Al Mubarok (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2023)
This study focuses on exploring the morality of students from two different environmental groups, namely students living in a pesantren environment and students living in a non-pesantren school at MTs Salafiyah Mojogeneng. Using a quantitative approach, this study used the descriptive analysis method to analyze and compare the two contexts. The study used two independent variables in its comparative analysis to examine the differences in morality between the two groups of students. The data collection methods used in this study included the use of documentation, interviews, and questionnaires to obtain the most accurate and comprehensive picture of the morality of students in both environments. In addition, the use of these multiple data collection methods also ensured the reliability and validity of the research findings. The results showed that the moral values of students living in a pesantren environment tended to be better than those of students living in non-pesantren schools. This finding indicates that the environment and teaching methods in pesantren may contribute to the development of higher moral values. Furthermore, this study also found a significant difference between the morality of students living in pesantren and non-pesantren in MTs Salafiyah Mojogeneng. This suggests that the context of residence and educational environment can play an important role in the formation of students' morality. Thus, this study concludes that there is a significant difference between the morality of students living in a pesantren environment and a non-pesantren school in MTs Salafiyah Mojogeneng.